The impact of earnings management on the performance of ASEAN banks - Wu Y.-C.; Wei Kiong Ting I.; Lu W.-M.; Nourani M.; Kweh Q.L. (Elsevier, 2023)
Southeast Asian financial liberalization policies have enthused both performance evaluation (a pro) and earnings management (a con). Using a sample of ASEAN commercial banks for the period 2007-2014, this study decomposes their banking performance into managerial and profitability efficiencies. An efficiency analysis reveals that Singaporean banks obtained the highest overall and profitability efficiencies, while Bruneian banks had the lowest rates of banking performance. In the stage of managerial efficiency, the most inefficient banks are those of the Philippines, whereas the greatest level is related to Malaysian banks. A frontier projection analysis suggests that Singaporean banks and Malaysian banks are generally more efficient in managing their expenditures and long-term assets in generating income in the long run. With respect to the con, a regression analysis indicates that loan loss provisions are negatively related to banking performance. Overall, it is advisable that policy makers with oversight function should promote performance evaluation from a multidimensional perspective, and keep an eye on estimates of loan loss provisions at banks over years because increases/decreases in loan loss provisions mean decreases/increases in net income or return on assets. 2015 Elsevier B.V.